This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Microeconomic Theory II Assignment 2: Risk and Information Solutions * February 15, 2007 Problem 1. Concerning Measures of Risk Aversion: Let u i : < → < ,i = 1 , 2 , be two strictly increasing, strictly concave, twice differentiable Bernoulli utility functions; and, let F : < → [0 , 1] be a cumulative distribution function for some realvalued random variable, ˜ y , which is the (positive or negative) reward from accruing some risky situation. So, agent i ’s preferences over gambles can be represented as follows: U i ( F ) = R u i ( y ) dF ( y ) ,i = 1 , 2. Define c ( F ; u i ) to be the certainty equivalent of the gamble represented by F for agent i : c ( F ; u i ) ≡ u 1 i [ R u i ( y ) dF ( y )] . We say that agent 1 is “more risk averse than agent 2” if and only if: ∀ F : c ( F ; u 1 ) 5 c ( F ; u 2 ). Prove that the following three claims are equivalent: (i.) Agent 1 is more risk averse than agent 2. (ii.) There exists an increasing concave function v : < → < such that, ∀ y ∈ < : u 1 ( y ) = v ( u 2 ( y )) . (iii.) ∀ y ∈ < : u 00 1 ( y ) u 1 ( y ) = u 00 2 ( y ) u 2 ( y ) Solution . • (ii.) ⇐⇒ (iii.): Notice that since both u 1 ( y ) and u 2 ( y ) are increasing we can always find an increasing function v ( · ) such that u 1 ( y ) = v ( u 2 ( y )). Taking the derivative in in this equation and using the chain rule we have that u 1 ( y ) = v ( u 2 ( y )) u 2 ( y ) . * Prepared by ¨ Omer ¨ Ozak ([email protected]), Department of Economics, Brown University. If you find any typos or mistakes please let me know, so that it can be fixed. 1 Microeconomic Theory II Solutions Taking logarithms on both sides and differentiating again we get u 00 1 ( y ) u 1 ( y ) = u 00 2 ( y ) u 2 ( y ) + v 00 v so that v 00 ≤ 0 if, and only if, u 00 1 ( y ) u 1 ( y ) ≤ u 00 2 ( y ) u 2 ( y ) . • (ii.) ⇒ (i.): By definition u 2 ( c ( F ; u 2 )) = R u 2 ( y ) dF ( y ), the hypothesis implies that u 1 ( c ( F ; u 1 )) = R v ( u 2 ( y )) dF ( y ). Since v ( · ) is concave, then Z v ( u 2 ( y )) dF ( y ) ≤ v Z u 2 ( y ) dF ( y ) ¶ . Putting the pieces together we get u 1 ( c ( F ; u 1 )) = Z v ( u 2 ( y )) dF ( y ) ≤ v Z u 2 ( y ) dF ( y ) ¶ = v ( u 2 ( c ( F ; u 2 ))) = u 1 ( c ( F ; u 2 )) and since u i ( · ) is strictly increasing, we have that c ( F ; u 1 ) 5 c ( F ; u 2 ). • (i.) ⇒ (ii.): Let v ( · ) again be the increasing function that makes u 1 ( y ) = v ( u 2 ( y )). By hypothesis c ( F ; u 1 ) 5 c ( F ; u 2 ) so that u 1 ( c ( F ; u 1 )) ≤ u 1 ( c ( F ; u 2 )). But this implies that Z v ( u 2 ( y )) dF ( y ) = u 1 ( c ( F ; u 1 )) ≤ u 1 ( c ( F ; u 2 )) =...
View
Full
Document
This note was uploaded on 07/06/2009 for the course ECON 206 taught by Professor G.loury during the Spring '07 term at Brown.
 Spring '07
 G.LOURY
 Microeconomics, Utility

Click to edit the document details